Ultrasonographic and radiographic features of a true gastrogastric intussusception with spontaneous resolution in a cat. Issue 6 (25th August 2022) - Huguet, Elodie E.; Spoldi, Elisa; Guarino, Aria; Cooke, Kirsten L.; Roberts, John F.
Abstract: An 11‐year‐old, female spayed, domestic shorthair cat with a 1‐week history of vomiting was diagnosed with a gastrogastric intussusception using ultrasound. Distinguishing ultrasonographic findings included invagination of the gastric fundus into the body and were correlated to radiographs acquired at the time of the evaluation. Spontaneous resolution of the gastrogastric intussusception was observed on a positive‐contrast upper gastrointestinal fluoroscopic study done the following day. Due to worsening comorbidities, which most significantly included chronic renal disease and pancreatitis, and declining quality of life, the patient was humanely euthanized 10 months later. Necropsy revealed no gross and histopathologic abnormalities associated with the stomach. A definitive cause for the intussusception remains unknown. Abstract : This report represents the first description of a true gastrogastric intussusception in a feline patient and highlights the utility of ultrasound and radiographs to achieve a diagnosis. While the clinical significance remained unknown, true gastrogastric intussusceptions in feline patients may be self‐limited.